The pharmacokinetics and pharmacodynamics of cisatracurium in critically ill patients with severe sepsis - Liu, Xin (Blackwell Science Inc, 2012)
AIM: To characterize the pharmacokinetics (PK) and pharmacodynamics (PD) of cisatracurium in critically ill patients with severe sepsis. METHODS: Blood samples were collected before and over 8 h after a single bolus dose of cisatracurium 0.1 mg kg(−1). Neuromuscular block was assessed by accelerometric peripheral nerve stimulation (TOF Watch). Plasma concentration and neuromuscular block data were fitted using population analysis. RESULTS: Steady-state volume of distribution was determined to be 111 ± 71 ml kg(−1) and plasma clearance was 5.2 ± 1.8 ml min(−1) kg(−1) in these patients with greater inter-patient variability compared with other populations. The time to maximum block (8.3 ± 2.9 min) and delay time of transferring from central to effect compartment (17.2 min) was much longer, while the maximum block (95.0 ± 6.3%) was less compared with those in other patient populations. The effect compartment concentration resulting in 50% of maximum effect (128 ± 58 ng ml(−1)) was larger than previously described. CONCLUSIONS: This study suggests that standard dosing of cisatracurium in patients with severe sepsis results in a slower patient response with a reduced effect. Use of a larger dose may overcome this reduced delayed response.